Development of the routine duration in artistic gymnastics from 1997 to 2019. (4th March 2021) - Seemann-Sinn, Alexander; Brehmer, Stefan; Naundorf, Falk; Wolfarth, Bernd
ABSTRACT: In this study, the development of routine duration (RD) in artistic gymnastics was investigated. Because of fundamental rule changes in 2006, the difference between the periods 1997–2005 and 2006–2019 and between the Olympic cycles (OC) over the entire period was examined. Therefore, 1387 routines were evaluated using video recordings. The results were: I) RD increased from 1997–2005 to 2006–2019 on pommel horse (36.0 to 44.0 s; p = 0.00), still rings (SR) (42.0 to 53.0 s; p = 0.00), parallel bars (PB) (35.0 to 50.0 s; p = 0.00), high bar (37.0 to 50.0 s; p = 0.00), uneven bars (UB) (32.5 to 36.0 s; p = 0.00), balance beam (83.0 to 85.0 s; p = 0.08) and floor female (87.0 to 89.0 s; p = 0.00), whereas floor male (67.0 vs. 67.0 s; p = 0.96) shows no differences; II) RD increase on SR from OC 2008 to OC 2012 (p = 0.00), at PB from OC 2012 to OC 2016 (p = 0.00), and reduced from OC 2012 to OC 2016 (p = 0.00) at UB. The increase of RD must be considered by coaches in order to prepare their athletes specifically for competitions.